An industrial quality study on Ito-Seisakusho Philippines Corporation - Escabel, Yvette (College of Engineering, 2004)
The study is a hands-on training for the study team on the application of Statistical Process Control (SPC) in an industrial set-up. The study site is a Japanese firm engaged in the production of dies and metal pressed products. The study focused only on the production of metal pressed parts. SPC tools were employed to come up with recommendations on process improvement. Control charts were generated to help enhance the company's process control. An analysis of the company's quality costs was also done to identify further improvements. The last part of this report summarizes the improvement recommendations the team has formulated. Recommendations include additional training of Die Setters and Material Feeding Operators; a documented Work Instruction on Proper Material Feeding; proposed revision to the layout of the Production Area; the use of partitioned boxes for storing, handling and packaging of raw materials and finished products; use of control charts in the Press Stamping Process; and a comprehensive review on the company's appraisal activities.